A clinico-observational study of intestinal stoma and their complications - Bhutra, Shyam; Singh, Amit; Darwal, Ramkishore; Jain, Piyush; Kala, Vineet (International Surgery Journal, 2019)
Background: The present study is designed to study the indications of intestinal stoma formation, type of stoma formation, complications of intestinal stoma made in patients under emergency or elective setting and postoperative care of the intestinal stomas. Methods: The study was carried out in Department of surgery at J. L. N. Medical College, Ajmer from January 2016 to September 2017. In this study only >12 years age patient were included. The data were collected prospectively and analysed. Results: It was observed that most patients were operated in emergency (90%) as compare to elective (10%) setting for the formation of intestinal stomas. The stoma was formed more in male (58%) as compared to female (42%). There were two peak age group 31-45 year and 45-60 years in which more stoma formation occur. The common indications for stoma were found to be ileal perforation with gangrenous ileum. The common stoma formed was ileostomy (64%) in compared to colostomy (34%). The loop stomas were formed in compared to end stoma and temporary stoma (84%) more formed compared to permanent stoma (16%). The most common complications were found to be skin excoriation (64%) as compared to other complications. Conclusions: Despite increasing surgical expertise, complications of intestinal stomas still occur frequently in all setups and result in high morbidity. Meticulous skin care with regular follow-up, early detection of complications with their timely management along with education and counselling can decrease morbidity.